A REVIEW ON BIOMETRIC CRYPTOSYSTEM USING FUZZY VAULT - V. Sujitha; D. Chitra (Pakistan Journal of Biotechnology, 2017)
Biometric framework helps to gather statistics from individual and it’s used to particularly find out the person with the physical-behavioral mechanism of the biometric qualities. The most challenge of biometric method is to provide the guarantee for storage space of the biometric templates without compromising the security and privacy. Biometric cryptosystem method is very helpful to secure traits from unauthorized access. The fuzzy vault is a famous and better biometric cryptography method to ensure the templates and its secret key in biometric frameworks. This paper reviews the various research work did in biometric cryptosystem using fuzzy vault.